Diversity and Applications of Endophytic Actinobacteria of Plants in Special and Other Ecological Niches - Singh, Radha; Dubey, Ashok K. (Frontiers in Microbiology, 2018)
Actinobacteria are wide spread in nature and represent the largest taxonomic group within the domain Bacteria. They are abundant in soil and have been extensively explored for their therapeutic applications. This versatile group of bacteria has adapted to diverse ecological habitats, which has drawn considerable attention of the scientific community in recent times as it has opened up new possibilities for novel metabolites that may help in solving some of the most challenging problems of the day, for example, novel drugs for drug-resistant human pathogens, affordable means to maintain ecological balance in various habitats and alternative practices for sustainable agriculture. Traditionally, free dwelling soil actinobacteria have been the subject of intensive research. Of late, symbiotic actinobacteria residing as endophytes within the plant tissues have generated immense interest as potential source of novel compounds, which may find applications in medicine, agriculture and environment. In the light of these possibilities, this review focuses on the diversity of endophytic actinobacteria isolated from the plants of extreme habitats and specific ecological niches. Furthermore, an attempt has been made to assign chemical class to the compounds obtained from endophytic actinobacteria. Potential therapeutic applications of these compounds and the utility of endophytic actinobacteria in agriculture and environment are discussed.